1983
DOI: 10.1007/bf01907440
|View full text |Cite
|
Sign up to set email alerts
|

Early shunting of 9 μm and 15 μm tracer microspheres from the acutely ischemic canine myocardium

Abstract: Recent reports have shown considerably differing results for myocardial shunting of 9 microns and 15 microns tracer microspheres (TMs) under various conditions. This could restrict the use of TMs for myocardial, especially collateral blood flow measurements. To determine the importance of coronary collateral blood flow and its early changes during the first 30 minutes after acute coronary artery occlusion (i.e. the 1st arrhythmic phase), we studied the shunting of 9 microns and 15 microns TMs from the ischemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Our study demonstrates that collateral flow rises continuously, both in the epi-and endocardium during the first 30 min of coronary occlusion (group 1), the increase being more pronounced in the first 10 rain. Factors influencing the results, such as TM shunting from the ischemic myocardium (22), extent of preexisting coronary collaterals 19,21) and special criteria for the identification of ischemic myocardium (24), might not have been considered in some of the studies cited.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our study demonstrates that collateral flow rises continuously, both in the epi-and endocardium during the first 30 min of coronary occlusion (group 1), the increase being more pronounced in the first 10 rain. Factors influencing the results, such as TM shunting from the ischemic myocardium (22), extent of preexisting coronary collaterals 19,21) and special criteria for the identification of ischemic myocardium (24), might not have been considered in some of the studies cited.…”
Section: Discussionmentioning
confidence: 97%
“…Thus we chose 9-~m-TM and studied their shunting under the special conditions of our experiments in advance (22). During the first 30 min of acute LAD occlusion 9-~m-TM shunting from the ischemic myocardium amounted at most to 1,2 %.…”
Section: Criticism Of the Tm Techniquementioning
confidence: 99%
“…The 'true' microsphere loss has been explained as lymphatic drainage (Jugdutt et al 1979) and/or arteriovenous shunting in the ischaemic myocardium (de Jonge et al 1980, Lekven & Andersen 1980. While some investigators claimed that microsphere loss was negligible and did not impair the results of myocardial blood flow measurement (Consigny et al 1982, Meesmann et al 1983), others demonstrated more profound losses, particularly with 9-pm spheres (Andersen et al 1983). These observations suggest the existence of narrow drainage routes for microspheres, supporting arteriovenous shunting as a probable mechanism behind the loss.…”
Section: Discussionmentioning
confidence: 99%